Beyond freedom and dignity - Skinner, Burrhus Frederic 1904- (New York, N.Y. Bantam Books, 1972)
Presents the argument that man's environment must be changed rather than man himself if the traditional goals of the struggle for freedom and dignity are to be reached.
A technology of behavior -- Freedom -- Dignity -- Punishment -- Alternatives to punishment -- Values -- The evolution of a culture -- The design of a culture -- What is man?
Includes bibliographical references.
Keywords: Personality and culture; Conditioned response; Control (Psychology)